ALTITUDINAL DISTRIBUTION OF ASTERACEAE INVADERS, AUSTROEUPATORIUM INULIFOLIUM AND AGERATINA RIPARIA, IN THE DISTURBED FOREST OF BATUKAHU NATURE RESERVE, BALI - Mukaromah, Laily (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 10 No 2 (2016), 2016)
Biological invasions are a major threat to biodiversity worldwide. Here, we aim to assess the occurrence of two invasive Asteraceae, Austroeupatorium inulifolium and Ageratina riparia , and the extent of their distributional range along altitudinal gradients in Mt Pohen, Batukahu Nature Reserve, Bedugul, Bali. The cover abundance of Austroeupatorium inulifolium and Ageratina riparia were measured by establishing 92 plot samples in four different forest conditions encompassed elevational ranges from the lowest (forest borders) to the highest elevation of Mt Pohen. Results showed that the abundance of both Asteraceae invaders were strongly correlated with disturbed habitats located at lower elevation. The forest borders at these forest sites were characterized by dense thicket of Austroeupatorium inulifolium and high abundance of Ageratina riparia . Both Asteraceae invaders reach their maximum altitudinal range up to the highest peak of the Mt Pohen. Results highlight that high abundance of these Asteraceae invaders which forms dense cover may lead to major forces of change in plant communities and forest ecosystem.
Keywords: Biological invasions; Asteraceae; Austroeupatorium inulifolium; maximum altitudinal range; Batukahu Nature Reserve